The Public and Private Epistolary Practice of Giovanni Querini, Ambassador of the Venetian Republic in Spain (1768-1773) - Javier ANTÓN PELAYO (Cuadernos Dieciochistas)
This article analyses the letter writing of Giovanni Querini, ambassador of the Republic of Venice in Spain from 1768 to 1772. Through examination of the official letters sent by him to his government and though the correspondence he maintained with his wife Caterina Contarini, the author describes the contingencies of the post, the duality of these epistolary discourses and the effectiveness of private letters for preserving marital intimacy and family sociability from a distance.